The Role Of Gentiana Olivieri Griseb Plant In Medicine And Folk Medicine, The Analysis Of Antidiarrheal Drugs In The Range Of Medicines Used In The Republic Of Uzbekistan - Mamajanova Erkinoy Abdurasulovna; A.M. Ernazarov (Genius Journals, 2024)
Today, the World Health Organization recommends the widespread use of medicinal herbs in medical practice in all countries. According to the World Health Organization, 80% of the world's population uses traditional medicine, and traditional medicine relies mainly on the plant kingdom. In Japan and China, the share of medicinal plants in medicine is very high. In European countries, there has also been a sharp increase in the use of plants in recent years. In this regard, the creation of an antidiarrheal drug based on the plant Gentiana Olivieri Griseb (Erbahor), which is mentioned in several folk remedies, as well as in the medical sources of Ibn Sina and Al-Razi and is used in folk practice, as well as the launch of industrial production is of paramount importance. In particular, in the treatment of diseases of the gastrointestinal tract and biliary tract
Keywords: Erbahor plant; diarrhea; alkaloid